2019
DOI: 10.1186/s12909-019-1592-0
|View full text |Cite
|
Sign up to set email alerts
|

The association between objectively-measured activity, sleep, call responsibilities, and burnout in a resident cohort

Abstract: Background When compared to the general US working population, physicians are more likely to experience burnout and dissatisfaction with work-life balance. Our aim was to examine the association of objectively-measured sleep, activity, call load, and gender with reported resident burnout and wellness factors. Methods Residents were recruited to wear activity tracker bands and complete interval blinded surveys. Results Of the 30 residents recr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 22 publications
0
24
0
1
Order By: Relevance
“…In the study “Using a Single Item to Measure Burnout in Primary Care Staff: A Psychometric Evaluation” 10 , a single question was proven to be a viable substitute to the MBI in assessing burnout and has been cited in multiple other studies for its use in assessing burnout among physicians. 11,12 The question is “Overall, based on your definition of burnout, how would you rate your level of burnout?”. The respondent is then given five descriptions of burnout with answers 1 and 2 being without burnout and answers 3, 4, and 5 with burnout.…”
Section: Methodsmentioning
confidence: 99%
“…In the study “Using a Single Item to Measure Burnout in Primary Care Staff: A Psychometric Evaluation” 10 , a single question was proven to be a viable substitute to the MBI in assessing burnout and has been cited in multiple other studies for its use in assessing burnout among physicians. 11,12 The question is “Overall, based on your definition of burnout, how would you rate your level of burnout?”. The respondent is then given five descriptions of burnout with answers 1 and 2 being without burnout and answers 3, 4, and 5 with burnout.…”
Section: Methodsmentioning
confidence: 99%
“…Another important and notable finding is that 42.5% of the residents are smokers, and along with the BMI and high stress level, these findings can explain why general well being subscale is low in nearly half of the surgical residents. On the contrary, a study conducted in US concluded that sleep hours and activity level have no association with burnout and stress level [17)]. This should shift the focus to other factors other than activity level or sleep hours, workload for instance.…”
Section: Discussionmentioning
confidence: 99%
“…Many factors have been associated with burnout among physicians including administrative workload, alignment of values between administrators and physicians, a sense of control over the workplace, excessive number of call days, high patient quotas, inattention to personal wellness, long work hours, mistakes, poor cohesiveness among coworkers, poor patient outcomes, and technology allowing “constant access” to work. [ 2 , 8 , 15 , 16 , 27 , 28 , 30 , 40 ]…”
Section: Factors Associated With Burnoutmentioning
confidence: 99%
“…Physicians are more likely to report burnout than the general population. [ 28 ] In fact, national burnout rates among physicians have been reported to be >50%. [ 40 , 46 ] Neurosurgeons are not immune to burnout, as reported rates in the specialty have ranged from 27% to 57%.…”
Section: Introductionmentioning
confidence: 99%